GENDER Platform needs assessment: Focus on capacity strengthening and influence - CGIAR GENDER Platform (CGIAR GENDER Impact Platform, 2020)
In November 2020, the GENDER Platform sent out an online survey to gender researchers across all CGIAR centers/alliances. One section of this survey, prepared by the Alliances Module, focused on researchers’ expressed needs to strengthen capacities to produce quality gender research that will achieve impact within CGIAR and beyond. Of the 39 respondents from 12 CGIAR centers who participated in the survey, 33 responded to the questions in this section. The results, presented below, focus on responses concerning the most important current needs and proposed strategies to address them.